ChemInform Abstract: Recent Advances in the Cyclization of N‐Heterocycles: The Role of Enabling Techniques. Issue 1 (7th January 2014) - Cravotto, G.; Tagliapietra, S.; Caporaso, M.; Garella, D.; Borretto, E.; Di Stilo, A.
Abstract Review: 44 refs.